Concrete-to-concrete bond strength. Influence of the roughness of the substrate surface - Júlio, Eduardo N. B. S. (2004)
An experimental study was performed to evaluate the bond strength between two concrete layers, for different techniques for increasing the roughness of the substrate surface. In a total of 25 slant shear specimens and 25 pull-off specimens the substrate surface was prepared by wire-brushing; sand-blasting; chipping with a light jackhammer; or were left as-cast against steel formwork. Three months later, the new concrete was added. Pull-off tests were performed to evaluate the bond strength in tension. Slant shear tests were conducted to quantify the bond strength in shear. Analysis of results indicated that: the highest value of bond strength was achieved with sand-blasting; pull-off tests are adequate to estimate the bond strength in situ; and pre-wetting the substrate surface does not seem to influence the bond strength.